Severe Gastroparesis following Radiofrequency Catheter Ablation for Atrial Fibrillation: Suggestion for Diagnosis, Treatment, and Device for Gastroparesis after RFCA - Dong Seok Lee; Sang Jin Lee (Case Reports in Gastrointestinal Medicine)
Gastroparesis following radiofrequency catheter ablation (RFCA) is a very rare complication, as only two cases have been reported in the English literature. A 42-year-old man underwent RFCA due to recurrent drug-resistant symptomatic atrial fibrillation. The patient complained of indigestion and early satiety 2 days after the procedure. Contrast-enhanced computed tomography and an upper gastrointestinal series of the abdomen showed a large amount of material remaining in the stomach area. All food material was removed by endoscopy, and the patient received medical treatment. We suggest a flow chart for diagnosis and treatment of AFGS based on the present case and previous cases. Endoscopic medical patent was designed on the basis of this case.